Proxy Wars in the New Dimensions of International Security - Hadzhiev, Boyan (Research Papers, 2019)
The focus of the article are the so-called proxy wars. Understanding and evaluating modern geopolitical clashes would be incomplete unless viewed through the prism of proxy wars. The violence is being increasingly "privatized". The war between states is giving way to prolonged internal conflicts without clear boundaries between communities, foreign interventions and the legitimacy of violence. In these conflicts non-state actors have become a major force for regional balances and an instrument for imposing the interests of various external geopolitical powers. The main participants, the importance of the state and the distinctive features of these wars, as well as arguments about the advantages and disadvantages of their use today, are being analyzed.
Keywords: Geopolitics; Proxy wars; International security